Nickel Promoted Palladium Nanoparticles for Electrocatalysis of Carbohydrazide Oxidation Reaction. Issue 28 (21st May 2019) - Guo, Min; Wang, Haining; Cui, Liting; Zhang, Jin; Xiang, Yan; Lu, Shanfu
Abstract: Carbohydrazide is a potential alternative to toxic hydrazine for fuel cell applications to overcome the challenges of storage and transportation of hydrogen. In this work, Ni‐alloyed Pd nanoparticles (NPs) with varied Pd–Ni ratios supported on carbon black (PdNi x /C) are prepared and their catalytic performance for the carbohydrazide electro‐oxidation reaction is investigated. The catalytic performance of PdNi x /C NPs is significantly improved in comparison to Pd/C NPs. The current density of PdNi x /C NPs with optimized Pd–Ni atom ratio can reach 3.26 A mg −1 metal at a potential of 0.4 V (vs reversible hydrogen electrode), which is an increase of 2.4 times compared to that of Pd/C. The density functional theory calculation indicates the enhanced catalytic activity is caused by the change of adsorption energy of carbohydrazide molecules on the metal surface. It exhibits a volcano relationship between the adsorption energy and the catalytic current density of PdNi x /C with varied Pd–Ni atom ratios. Abstract : Nickle‐alloyed Palladium nanoparticles with varied Pd–Ni ratios are prepared, which exhibit significantly improved electrocatalytic performance toward carbohydrazide oxidation than Pd. The density functional theory calculation reveals the proposed mechanism is the change of adsorption of carbohydrazide molecules on the metal surface. It exhibits a volcano relationship between the adsorption energy and the catalytic activity with varied Pd–Ni ratios.